Case study comparison of functional vs. organic stability approaches for assessing threat potential at closed landfills in the USA. (May 2018) - O'Donnell, Sean T.; Caldwell, Michael D.; Barlaz, Morton A.; Morris, Jeremy W.F.
Highlights: Functional stability criteria focus on site-specific threats. Organic stability criteria do not consider site-specific threats. Organic stability criteria generally require longer aftercare periods. Functional stability criteria are more reasonable and defensible. Both approaches are protective of human health and the environment. Abstract: Municipal solid waste (MSW) landfills in the USA are regulated under Subtitle D of the Resource Conservation and Recovery Act (RCRA), which includes the requirement to protect human health and the environment (HHE) during the post-closure care (PCC) period. Several approaches have been published for assessment of potential threats to HHE. These approaches can be broadly divided into organic stabilization, which establishes an inert waste mass as the ultimate objective, and functional stability, which considers long-term emissions in the context of minimizing threats to HHE in the absence of active controls. The objective of this research was to conduct a case study evaluation of a closed MSW landfill using long-term data on landfill gas (LFG) production, leachate quality, site geology, and solids decomposition. Evaluations based on both functional and organic stability criteria were compared. The results showed that longer periods of LFG and leachate management would be required using organic stability criteria relative to an approach based on functional stability. These findings highlight the somewhat arbitrary and overly stringent nature of assigning universal stability criteria without due consideration of the landfill's hydrogeologic setting and potential environmental receptors. This supports previous studies that advocated for transition to a passive or inactive control stage based on a performance-based functional stability framework as a defensible mechanism for optimizing and ending regulatory PCC.